Implementasi Pembuatan Modul Ajar Berbasis Artificial Intelligence (Ai) di SDN 17 Pasir Permit - Indriani, Ririn; Samin Lubis, Mara; Putri Lubis, Annisa; Lestari, Ayu; Riadi, Salamat; Izzati, Aufi Nadrah; Fatmawati, Sri Ayu; Amalia, Ariza; Rahmadani Lubis, Khaiyirah; Purnama Sari, Reni (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
Technological developments in the world of education have created various innovations to support the learning process, one of which is in the creation of teaching modules using AI, this research uses qualitative research methods because it aims to understand in depth how the implementation of AI-based teaching modules, this workshop was held at SDN 17 Pasir Permit, through the presentation of material and direct practice, so that this workshop is able to help teachers to create modules Teaching more effectively and efficiently using AI so that teachers' tasks can be minimized.